A free people's suicide sustainable freedom and the American future - Guinness, Os. (Downers Grove, Ill. : IVP Books, 2012)
Cultural observer Os Guinness examines the American founders' belief that the American republic could remain free forever. He argues that contemporary views of freedom are unsustainable because they undermine the conditions necessary for freedom to thrive, and he proposes steps to restore sustainable freedom.
What kind of people do you think you are? -- Always free, free always -- Using history to defy history -- The golden triangle of freedom -- The completest revolution of all -- An empire worthy of free people -- The eagle and the sun.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Liberty -- Religious aspects -- Christianity; Christianity -- United States -- 21st century; United States -- Politics and government -- 21st century; United States -- Forecasting; Christianity; Forecasting; Liberty -- Religious aspects -- Christianity; Political science; United States; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; 2000 - 2099; Electronic books